Montessori Preschool Elevates and Equalizes Child Outcomes: A Longitudinal Study - Lillard, Angeline S.; Heise, Megan J.; Richey, Eve M.; Tong, Xin; Hart, Alyssa; Bray, Paige M. (Frontiers in Psychology, 2017)
Quality preschool programs that develop the whole child through age-appropriate socioemotional and cognitive skill-building hold promise for significantly improving child outcomes. However, preschool programs tend to either be teacher-led and didactic, or else to lack academic content. One preschool model that involves both child-directed, freely chosen activity and academic content is Montessori. Here we report a longitudinal study that took advantage of randomized lottery-based admission to two public Montessori magnet schools in a high-poverty American city. The final sample included 141 children, 70 in Montessori and 71 in other schools, most of whom were tested 4 times over 3 years, from the first semester to the end of preschool (ages 3 to 6), on a variety of cognitive and socio-emotional measures. Montessori preschool elevated children's outcomes in several ways. Although not different at the first test point, over time the Montessori children fared better on measures of academic achievement, social understanding, and mastery orientation, and they also reported relatively more liking of scholastic tasks. They also scored higher on executive function when they were 4. In addition to elevating overall performance on these measures, Montessori preschool also equalized outcomes among subgroups that typically have unequal outcomes. First, the difference in academic achievement between lower income Montessori and higher income conventionally schooled children was smaller at each time point, and was not (statistically speaking) significantly different at the end of the study. Second, defying the typical finding that executive function predicts academic achievement, in Montessori classrooms children with lower executive function scored as well on academic achievement as those with higher executive function. This suggests that Montessori preschool has potential to elevate and equalize important outcomes, and a larger study of public Montessori preschools is warranted.